Music-Based Services for Young People Experiencing Homelessness: Engaging Strengths and Creating Opportunities. Issue 1 (January 2017) - Kelly, Brian L.
This study explores a music studio in a transitional living program for young people experiencing homelessness. Using an ethnographic approach, data were collected to explore: (a) young people's experiences in the music studio, (b) the meanings they attach to their experiences, and (c) whether involvement in the studio engages their strengths. Study findings present a compelling narrative that supports the use of music-based services for young people experiencing homelessness as a way to engage their strengths and foster important opportunities for connection, engagement, and creative expression. Findings highlight the importance of challenging prescriptive notions of homeless youth and developing services that engage their strengths.